Pengaruh Keterampilan Interpersonal, Pengalaman Kerja, Integritas dan Keterikatan Kerja terhadap Kinerja Penyuluh Pertanian - Didit Darmawan; Rahayu Mardikaningsih (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Agricultural Extension Officers are agricultural service officers who are tasked with helping farmers run farming businesses through an extension system as a form of learning activity for farmers and agricultural entrepreneurs so that they can help and organize themselves when looking for and using information about markets, capital, technology, and other resources to be able to developing business efficiency, productivity, welfare and income, as well as developing the level of awareness to preserve the environment. Agricultural instructors must have managerial and technical competencies because agricultural instructors must have technical capabilities related to agriculture, and managerial capabilities include the ability to manage work to carry out extension services. To carry out outreach activities, qualified instructors are needed. The performance of the extension agent determines the effectiveness of the extension activity so that it is necessary to determine the determinants of the performance of the extension worker. The research was conducted in Lumajang Regency, East Java. This study resulted in four findings, namely: (1) interpersonal skills have a significant role in performance; (2) the performance of the instructor is not significantly affected by work experience; (3) integrity has a significant impact on the performance of extension workers; (4) the ups and downs of the performance of the extension worker get the role of work engagement